Inclusive leadership for sustainable development in times of change [version 2; peer review: 1 approved, 2 approved with reservations] - Sulaiman Olusegun Atiku; Richmond Anane-Simon (Routledge Open Research)
This article explores the concept of inclusive leadership as a key enabler for sustainable development, especially in times of change. A literature review approach was adopted drawing on relevant research and best practices. The article identifies the key competencies and behaviors that inclusive leaders should demonstrate and it explores the challenges and opportunities of leading inclusively in times of change. According to the findings of the study, inclusive leadership can promote sustainable development by encouraging creativity, enhancing organizational effectiveness and fostering social and environmental responsibility. The article concludes with a call to action for individuals and organizations to embrace inclusive leadership for a sustainable future.